Accelerated testing of mechanical and chemical effect of the environment on wear resistance of parts of tribocouples under complex dynamic loading - Tsyganov, V.V.; Sheyko, S.P.; Shalomeev, V.A.; Vodennikova, O.S.; Kulabnieva, O.A. (Karaganda University named after academician E.A.Buketov, 2023)
The wear of tribocouplings parts under complex dynamic loading conditions is considered. A methodology for accelerated testing of friction pairs under multi-component dynamic loading is offered. The designs stand for modeling the processes of contact interaction, and studies of the wear resistance of tribocouplings, which operate under complex dynamic loading conditions with various lubricating and cooling media, are presented. The results of the impact assessment of mechanic and chemical transformations in the contact zone of tribological interfaces for wear resistance according to the developed method are presented. The variable effectiveness evaluation of the degradation influence products of macromolecular compounds in the composition of cutting fluid on wear resistance of metals in the contact zone of tribocouplings are analysed. The use of the presented materials allows rationally selecting friction pair materials for given operating conditions, developing new wear-resistant materials and coatings, lubricant composition and cooling mediums.
Keywords: wear; complex loading; friction; stand; polymer